Climate Innovation Through Interactive Ecosystem Summits (Cities 4.0): Consolidated report on innovation challenges and joint business opportunities. Deliverable 2.1. - Vehmas Jarmo (European Commission, 2025)
This consolidated report on innovation challenges and joint business opportunities is part of Cities 4.0 Work Package 2 “Understanding and translating cities’ challenges and society needs to business opportunities”. Turku Science Park Ltd is responsible for this WP and does cooperation with the University of Turku, Finland Futures Research Centre.
The key stakeholders represent the main sectors identified from the cities’ applications for NetZeroCities (Cities 4.0 deliverable 2.1. These sectors include energy, transport, waste/wastewater, and digitalization/smart city activities. The identified stakeholders may represent also other sectors since the innovation potential and business opportunities are not necessarily limited to the abovementioned important sectors identified by the cities.